Pemanfaatan Limbah Peluru BB pada Pengembangan Desain Handstop Grip dan Handguard Cover Airsoftgun - Yulius Wisdam Arya Prasetyo; Daniel Pandapotan; Marcellino Aditya Mahendra (DEFENDONESIA, 2025)
Airsoft is one of the supporting activities carried out to train accuracy and dexterity before fighting using replica guns and plastic BB bullets. This activity has contributed to the addition of plastic waste. After finishing airsoft training, BB bullets are simply thrown away without further processing. The author is concerned about this waste so that the problem of how to process plastic waste from BB bullets can be done through products that are reused by airsoft gun users. The author needs to analyze the characteristics of the material and texture of the results of processing BB bullet waste. The author developed a BB bullet waste processing technique so that it can be formed into a functional product. The author designs and produces airsoft gun accessory products based on user preferences. The methods used include experimental and SCAMPER. Experimental consists of processing BB bullet waste with the addition of nets to increase the strength and aesthetics of the product. The processed results are then tested for material characteristics. Furthermore, product design is carried out using the SCAMPER method and ends with the manufacture of a prototype. The study succeeded in obtaining the characteristics of processed BB bullet waste material that is hard and strong from BB bullets so that it can be formed, remains waterproof, and also has a unique texture and color. This processed material is then applied to the manufacture of airsoft gun accessory products in the form of hand guard covers and hand stop grips. The resulting product has an innovative design, combining the concept of strong texture and unique military aesthetics. The potential of the product can be further utilized as a public attraction to the resilience of the universe pioneered on fun occasions such as airsoft.